Land Deed Dispute, Camden County, 1882 - State of Georgia, Camden County (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1882)
Land Deed Dispute, Camden County, 1882. Hand written record on ruled paper. Affidavit of Isabel Adams regarding Crow Harbor tract and Asa J. Stafford, son of Nathanial B. Stafford. Camden County, Georgia. December 4, 1882. 2 pages.
1 electronic document [PDF/A]. Includes TIFF and JP2 images. Digitized by the Digital Library of Georgia, September 2019.
Keywords: Deeds; Camden County (Ga.); Court Records; Records and correspondence